2019
DOI: 10.1111/pin.12756
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of fatty acid binding protein‐4 in the invasive ductal carcinoma of the breast

Abstract: We conducted this study to identify clinico‐pathologic and prognostic factors that are associated with fatty acid binding protein‐4 (FABP4) and to discuss its therapeutic potentials in patients with breast cancer (BC). In a total of 75 patients with an established diagnosis of invasive ductal carcinoma of the breast, we performed a retrospective analysis of the medical records and analyzed their immunohistochemical findings. Following evaluation of baseline and clinico‐pathological characteristics such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…High expression of FABP4 contributes to the poor prognosis in Ovarian Carcinoma, nonsmall cell lung cancer, Pancreatic Ductal Adenocarcinomas, and hepatocellular carcinoma [ 30 33 ]. There was a significant correlation between FABP4 expression and tumor grade [ 34 ]. This study demonstrated that ABCA8 and FABP4 were downregulated in STAD, and high expression of ABCA8 and FABP4 was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of FABP4 contributes to the poor prognosis in Ovarian Carcinoma, nonsmall cell lung cancer, Pancreatic Ductal Adenocarcinomas, and hepatocellular carcinoma [ 30 33 ]. There was a significant correlation between FABP4 expression and tumor grade [ 34 ]. This study demonstrated that ABCA8 and FABP4 were downregulated in STAD, and high expression of ABCA8 and FABP4 was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…FAPB4 is a tumor suppressor, the expression of FABP4 is significantly correlated with tumor stage, disease-free survival (DFS) and overall survival (OS) [ 21 ]. Especially, overexpression of FABP4 in tumor-associated macrophages promotes breast cancer growth [ 22 ], and blocking FABP4 expression in endothelial cells reduces angiogenic activity and tumor growth [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 increases breast cancer cell proliferation in MCF-7 (luminal breast cancer) and MDA-MB-231 triple-negative breast cancer cells, but activation of fatty acid transporters only occurs in MCF-7 luminal breast cancer cells [ 94 ]. A previous study showed no correlation between clinicopathologic parameters, including ER, PR, and HER2 status, and FABP expression [ 95 ]. FABP4 also plays a critical role in the metastasis and stromal interaction of MDA-MB 231, triple-negative breast cancer cells (TNBC) [ 96 ].…”
Section: Discussionmentioning
confidence: 99%